Pengaruh Komunikasi Organisasi Dan Kompensasi Terhadap Kepuasan Kerja Karyawan Bank Syariah Indonesia (BSI) KCP Stabat Berdasarkan Perspektif Islam - Evelyne Vagittha Tarigan; Zuhrinal M. Nawawi (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the effect of organizational communication and compensation on job satisfaction of Bank Syariah Indonesia (BSI) KCP Stabat employees based on an Islamic perspective. This research methodology is descriptive quantitative, where the focus of this research is to find out the special problems studied from all aspects of personality that are pleasing to the object of research, this research is often called casuistic observation research. The results of the study show that organizational communication variables have a significant effect on job satisfaction variables separately or separately. Meanwhile, the compensation variable has no significant effect on the job satisfaction variable separately or individually. Based on an Islamic perspective, Bank Syariah Indonesia (BSI) KCP Stabat Concerning the Influence of Organizational Communication and Compensation on Employee Job Satisfaction is in accordance with Islamic teachings, namely good communication between fellow employees resulting in a significant influence on job satisfaction. Meanwhile, the compensation provided by Bank Syariah Indonesia (BSI) KCP Stabat is appropriate and in accordance with the hard work of employees.